A Juridical Review on the Regulation of Criminal Offenses in Cases of Violent Theft from the Perspective of the Criminal Code - Bestavianor, Arief; Sriono, Sriono; Toni, Toni (International Journal Labs, 2024)
This study aims to analyze and understand the criminal arrangements in the crime of theft with violence according to the Criminal Code (KUHP) and its application in verdict number 728 K/Pid/2019. The approach used in this research is a normative legal approach, which involves the study of legislation, theories, and related concepts to obtain relevant data from the community. This research uses primary and secondary legal data as sources of legal materials. The results show that the crime of theft with violence is regulated in Article 365 of the Criminal Code with various levels of punishment based on the conditions that accompany the act, ranging from a nine-year prison sentence to the death penalty or life imprisonment. For example, the punishment will be more severe if the act is committed at night, by more than one person, by dismantling, or if it results in severe injury or death. In the case study of decision number 728 K/Pid/2019, the judge issued a verdict indicating that the defendant was found guilty of committing the crime of theft with violence. The verdict is considered to have fulfilled the applicable provisions formally and materially in the legislation. The implications of this research show the importance of a deep understanding of the regulation and application of the law on the crime of theft with violence to ensure justice and consistency in law enforcement. This research also emphasizes the need to increase legal awareness among the public regarding the severe sanctions faced by perpetrators of violent theft